Marine invertebrates as proxies for early kelp use along the western coast of South America - Alcalde, Verónica; Flores, Carola; Guardia, Javiera; Olguín, Laura; Broitman, Bernardo R. (Frontiers in Earth Science, 2023)
Coastal societies have lived at the seaward edge of the Atacama Desert since at least 12000 years ago. Up to date, kelp forest ecosystems provide evidence for important subsistence activity along the entire Chilean coast through fishing and gathering. Despite their importance, especially in hyperarid contexts with limited plant abundance, there is scarce evidence of kelp in archaeological contexts, hampering the study of kelp use in the past. In the present study we use the presence of small marine invertebrates, inhabitants of stipes and holdfasts of macro algae, as proxies that indicate kelp presence in the past. We analyze samples of three species of snails (Tegula atra, Tegula tridentata and Diloma nigerrima) and one limpet (Scurria scurra) from nine archaeological sites dated between 7000 and 500 cal years BP located around the area of Taltal (25°Lat S). Modern samples of these species were collected to reconstruct the size of fragmented archaeological shells and subsequently estimate the size of harvested kelps. Through this approach, we estimated size and relative abundance of kelp used by coastal groups that inhabited the southern part of the Atacama Desert over around 6500 years. Our results are a contribution to the scarce information on the presence and use of kelp in the Americas prehistory and contribute to comparative perspectives with other areas of the world where the use of kelp by humans in the past has already been explored.